Das endoplasmatische Retikulum in der Mitose: ein wandelbares Netz - Schlaitz, Anne-Lore (Biospektrum, 2020)
In order to divide successfully, cells need to reorganize their interior including membrane-bound organelles such as the endoplasmic reticulum (ER). The ER serves as sink and source for the nuclear envelope and undergoes distinct transformations in its morphology and dynamics during cell division. To fully appreciate the functions of ER remodeling during cell division it will be essential to first achieve a detailed understanding of the underlying molecular mechanisms.
Gesehen am 09.11.2021